2010
DOI: 10.1136/jnnp.2009.182824
|View full text |Cite
|
Sign up to set email alerts
|

Microvascular decompression of the trigeminal nerve in the treatment of SUNCT and SUNA

Abstract: Medically intractable SUNCT and SUNA subjects with a demonstrable aberrant arterial loop impinging on the trigeminal nerve on neuroimaging may benefit from microvascular decompression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
44
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 25 publications
1
44
0
Order By: Relevance
“…Growing evidence also supports aetiological similarities with trigeminal neuralgia because of the significant proportions of patients with SUNCT and SUNA showing a neurovascular conflict with the trigeminal nerve [4]. Preliminary data demonstrate the efficacy of MVD of the trigeminal nerve in SUNCT and SUNA, suggesting the possible role of damage to the trigeminal sensory root in the pathophysiology of these disorders [39]. This underlying common mechanism could account for the striking clinical similarities between these conditions, supporting the hypothesis that SUNCT, SUNA and trigeminal neuralgia represent variants of the same disorder.…”
Section: Resultsmentioning
confidence: 88%
“…Growing evidence also supports aetiological similarities with trigeminal neuralgia because of the significant proportions of patients with SUNCT and SUNA showing a neurovascular conflict with the trigeminal nerve [4]. Preliminary data demonstrate the efficacy of MVD of the trigeminal nerve in SUNCT and SUNA, suggesting the possible role of damage to the trigeminal sensory root in the pathophysiology of these disorders [39]. This underlying common mechanism could account for the striking clinical similarities between these conditions, supporting the hypothesis that SUNCT, SUNA and trigeminal neuralgia represent variants of the same disorder.…”
Section: Resultsmentioning
confidence: 88%
“…This supported the notion of MVD being a potential treatment for these conditions. To date, 10 case reports and a case series of nine patients with medically intractable SUNCT and SUNA patients, who underwent MVD of the trigeminal nerve, have been reported [26,[30][31][32][33][34][35]. After a median follow-up of 14 months (range 0.5-32 months), 12 of 19 (63 %) of cases were pain free, whereas in the remaining patients, the procedure had little or no effect.…”
Section: Microvascular Decompression Of the Trigeminal Nervementioning
confidence: 99%
“…Willams et al described 9 patients with vascular compression of the trigeminal nerve who underwent decompressive surgery and reported that 6 of the 9 patients were rendered pain-free. The remaining patients did not have any observed benefit [31]. Additional cases have been reported of patients attaining pain freedom from microvascular decompression [32][33][34].…”
Section: Trigeminal Nerve Decompressionmentioning
confidence: 95%
“…Despite reported good outcomes, it is important to consider potential adverse events for such invasive procedures used in the treatment of SUNCT and SUNA. In the case series by Williams et al, 1 patient suffered ipsilateral hearing loss post procedure [31]. Black and Dodick identified 2 patients who had undergone both gamma knife radiosurgery and microvascular decompression without sustained benefit.…”
Section: Trigeminal Nerve Decompressionmentioning
confidence: 99%